Acute Exposure to Cigarette Smoking Followed by Myocardial Infarction Aggravates Renal Damage in an In Vivo Mouse Model. (22nd October 2017) - Kobeissy, Firas; Shaito, Abdullah; Kaplan, Abdullah; Baki, Lama; Hayek, Hassan; Dagher-Hamalian, Carole; Nehme, Ali; Ghali, Rana; Abidi, Emna; Husari, Ahmad; Zeidan, Asad; Zouein, Fouad A.; et al.
Abstract : Cigarette smoking (S) is a risk factor for progressive chronic kidney disease, renal dysfunction, and renal failure. In this study, the effect of smoking on kidney function was investigated in a mouse model of myocardial infarction (MI) using 4 groups: control (C), smoking (S), MI, and S+MI. Histological analysis of S+MI group showed alterations in kidney structure including swelling of the proximal convoluted tubules (PCTs), thinning of the epithelial lining, focal loss of the brush border of PCTs, and patchy glomerular retraction. Molecular analysis revealed that nephrin expression was significantly reduced in the S+MI group, whereas sodium-hydrogen exchanger-1 (NHE-1) was significantly increased, suggesting altered glomerular filtration and kidney functions. Moreover, S+MI group, but not S alone, showed a significant increase in the expression of connective tissue growth factor (CTGF) and fibrotic proteins fibronectin (FN) and α -smooth muscle actin (SMA), in comparison to controls, in addition to a significant increase in mRNA levels of IL-6 and TNF- α inflammatory markers. Finally, reactive oxygen species (ROS) production was significantly accentuated in S+MI group concomitant with a significant increase in NOX-4 protein levels. In conclusion, smoking aggravates murine acute renal damage caused by MI at the structural and molecular levels by exacerbating renal dysfunction.